Pembuatan Kue Talam Umbi Talas (Colocasia Esculenta) dengan Penambahan Kulit Buah Naga - Adilla Shafa Az Zahra; Ira Handayani; Ndaru Prasastono (Garina, 2025)
The present study was conducted to assess consumer acceptability of taro-based kue talam supplemented with dragon fruit peel and to describe the ingredient composition and nutritional content of the preferred formulation. An experimental design comprising three formulations was employed. The resulting products were subjected to an organoleptic evaluation by untrained panelists, covering the attributes of color, aroma, taste, texture, and overall acceptability. The findings indicated that Formula A received the highest preference scores. The bottom layer of Formula A consisted of 650 g taro, 130 g dragon fruit peel, 250 ml coconut milk, 110 g tapioca flour, 230 g rice flour, 250 g granulated sugar, ½ tsp salt, and 1 tsp vanilla. The top layer comprised 350 ml coconut milk, 25 g granulated sugar, 30 g tapioca flour, 60 g rice flour, and ½ tsp salt. Nutritional analysis per 100 g of product revealed carbohydrate and protein contents of 48.45% and 2.515%, respectively. The study concludes that taro-based kue talam enriched with dragon fruit peel has promising acceptability and may be considered a potential innovation in local tuber-based food products. Further research is recommended to include cost analysis for pricing determination.